Pay Fairness: Percepsi, Anteseden, dan Konsekuensi - Tien Suhartini (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2022)
Various factors have caused Pay Fairness to become a much more important and challenging issue for reward leaders in recent years. Rewards equity and constructs related to fairness and salary equity are closely related to employee attitudes and behavior. This paper is a review of articles from international journals on payment equity. Justice in this paper is taken from the word’s fairness, justice, and equity, while the opposite, injustice, is taken from unfairness, injustice, and inequity. The purpose of this paper is to obtain one of the variables, along with the indicators, which will be used in research on Pay Fairness. Apart from perceptions, antecedents, and consequences, there are also several theories and grand theories referred to in assessing the fairness of payments. The results show that the antecedents of fairness of payments are efforts to close gender gaps, change attitudes towards transparency, increase workforce diversity, increase access to information, and sensitivity to employee preferences. The consequences of pay transparency are divided into 1) positive, such as increasing motivation, involvement, loyalty, and understanding how payments are determined and knowing how to maximize payments; and 2) negative, such as creating jealousy and conflict, dishonesty, perceptions of injustice, and loss of privacy